Peran Digital Upskilling Dan Reskilling Dalam Peningkatan Kapabilitas Sdm Pariwisata - Ayu Suwita Yanti (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The accelerated development of digital technologies has generated significant implications for human resource management practices within the tourism industry. These changes necessitate continuous adjustments in workforce competencies to effectively respond to increasingly complex and technology-driven industry dynamics. Within the framework of Industry 5.0, digital transformation is no longer understood merely as an effort to optimize operational efficiency, but rather as a strategic process aimed at reinforcing the role of humans as the central actors of innovation, oriented toward human values and sustainability. This article aims to comprehensively examine the role of digital upskilling and reskilling as strategic approaches to developing tourism human resource capabilities in response to the adoption of digital technologies, artificial intelligence, and shifts in tourist preferences and behaviors. The study employs a literature review approach by analyzing various empirical and conceptual studies relevant to human resource development, digital transformation, and sustainable tourism. The findings indicate that digital upskilling and reskilling play a strategic role in shaping core competencies of tourism human resources that are adaptive, creative, and highly competitive. Beyond enhancing digital technical skills, these approaches also contribute to strengthening social, cognitive, and innovative capabilities among tourism workers. The study underscores that the development of tourism human resources aligned with the principles of human-centric innovation is a critical prerequisite for ensuring the sustainability and competitiveness of the tourism industry in the era of Industry 5.0.